A CRITICAL ANALYSIS STUDY ON OTALGIA MANAGEMENT BY GARLIC DROPS AND BENZOCAINE DROPS- AN ATTEMPT TO COMPARE THE EFFICACY OF MODERN AND AYURVEDA MEDICINE IN A SINGLE AILMENT - Rathi.S; Sucha lakshmi R (International Journal of Ayurveda and Pharma Research, 2020)
Otalgia or ear ache is a symptom which will hamper the daily activities of individual, and a cause of unease or discomfort. There might not be any single individual who has not affected with earache in their lifetime, atleast once in their span of life..Even today there is no specific permanent remedy to this condition in advance modern medical system despite of some Otogesics which will only mask the pain. The common Over the Counter medicines available on medical stores are having side effects on continuous usage. So there is a need for safe Ayurvedic medicine which can acts better like modern analgesics but less side effects. Methodology: In this comparative study of Lasuna putapaka swarasa (Garlic Drops) and Benzocaine Otogesic drops, 40 patients of Otalgia were randomly selected and divided to two groups of 20 patients each. Group A was treated with the ear drops of Lasunaputapaka swarasa (Garlic Drops) and Group B was treated with Benzocaine Otogesic ear drops. Observations: It was observed in the present study that Group A showed better results in reducing the symptoms of Otalgia. Re-occurrence of symptoms were merely less in Group A patients compared to Group B patients. Conclusion: There is a false assumption that Ayurvedic medicines are slow acting and desperately using for pain management and acute conditions. But this study throwing a light to substantiate that, Ayurvedic medicines are potent enough to manage acute otalgia also, just like Otogesics in Modern Medical Science. The study revealed that the re-occurrence rate of symptoms was very less in patients who used Garlic drops and was safe acting also.